2007
DOI: 10.1002/pmic.200600756
|View full text |Cite
|
Sign up to set email alerts
|

A combined dataset of human cerebrospinal fluid proteins identified by multi‐dimensional chromatography and tandem mass spectrometry

Abstract: Human cerebrospinal fluid (CSF) is an important source for studying protein biomarkers of age-related neurodegenerative diseases. Before characterizing biomarkers unique to each disease, it is necessary to categorize CSF proteins systematically and extensively. However, the enormous complexity, great dynamic range of protein concentrations, and tremendous protein heterogeneity due to post-translational modification of CSF create significant challenges to the existing proteomics technologies for an in-depth, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 34 publications
4
91
0
Order By: Relevance
“…Concordance in protein ratios and overall trends is greatest between the two laboratories identifying the highest number of proteins. This supports an argument that future studies with resource limitations should emphasize the depth of protein coverage and include multiple laboratories only if their experimental methods complement each other in terms of the protein observations (30). Our study also suggests that data integration plays a central role in studies to identify biomarkers as statistical significance could not have been demonstrated without the ability to evaluate changes in predefined groups of proteins using the gene set enrichment analysis (GSEA) approach.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Concordance in protein ratios and overall trends is greatest between the two laboratories identifying the highest number of proteins. This supports an argument that future studies with resource limitations should emphasize the depth of protein coverage and include multiple laboratories only if their experimental methods complement each other in terms of the protein observations (30). Our study also suggests that data integration plays a central role in studies to identify biomarkers as statistical significance could not have been demonstrated without the ability to evaluate changes in predefined groups of proteins using the gene set enrichment analysis (GSEA) approach.…”
supporting
confidence: 75%
“…In practice, one can use these values as filters to generate lists by lab for protein groups that significantly change with disease status. Because of limitations in the accuracy and comprehensiveness of any one data set due to the complex nature of the samples (19,30) and current technology (42), a combination of these results across labs using completely different experimental designs and proteomics platforms will improve the accuracy, consistency, and comprehensiveness of protein candidate lists. Here we used a method described under "Experimental Procedures" of first performing a comprehensive search on all applicable data and then synthesizing the quantitation results.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, studies have been published with numerous identities and quantities of CSF proteins. Pan and co-workers were able to identify 2,594 proteins in well-characterized pooled human CSF samples using strict proteomics criteria with a combination of linear trap quadrupole LTQ-FT (Thermo Fisher Scientific, Bremen, Germany) and MALDI TOF/TOF equipment (14). They were also able to quantify several proteins using a targeted LC MALDI TOF/TOF approach (15).…”
mentioning
confidence: 99%
“…Finally, an exhaustive view of CSF proteome was obtained by Fourier transform ICR which could identify more than 4000 different proteins [23,24].…”
Section: Proteomics Analysis Of the Normal Csf Proteomementioning
confidence: 99%